Changes in Granular Swelling and Rheological Properties of Food Crop Starches Modified by Superheated Steam. (23rd September 2018) - Liu, Chengmei; Yan, Xiaoyan; Xu, Xingfeng; Guo, Baozhong; Yang, Rong; Chen, Jun; Zhong, Yejun; Luo, Shunjing; Xu, Jianguo; Wu, Jianyong
Abstract : Conventional hydrothermal modification of starches is a time‐ and energy‐consuming process. In this study, superheated steam treatment (SST) is used to modify the granular swelling and rheological properties of rice, corn, wheat, and potato starches, and the dependence of these modifications on starch sources is investigated. SST causes a decrease in granular swelling and structural recovery of gel network regardless of the starch source. The long‐term stability of all the starch gels is improved by SST, but their daubing performance may be degraded. In contrast, the responses of the starch gels to deformation and shear vary depending on the starch sources. The deformability, structural strength, and viscosity of corn, wheat, and potato starch gels are decreased by SST, while those of rice starch gel are increased. The shear‐thinning behavior of rice and wheat starch gels is strengthened and that of corn and potato starch gels is weakened by SST. Considering the high thermal efficiency of SS and the short treatment time (1 h) used in this study, SS treatment can be a superior alternative to conventional hydrothermal modification. Abstract : Conventional hydrothermal modification of starches is a time‐ and energy‐consuming process. Superheated steam treatment (SST) is used to modify the granular swelling and rheological properties of rice, corn, wheat and potato starches, and the dependence of these modifications on starch sources is investigated. The results show that the SST could be a superior alternative to conventional hydrothermal modification.